First measured optical image of Cerenkov-light in water during irradiation of neutron beam from boron neutron capture therapy (BNCT) system. (August 2021) - Yabe, Takuya; Yamamoto, Seiichi; Hu, Naonori; Kanai, Yasukazu; Tanaka, Hiroki; Ono, Koji
Abstract: Optical imaging that detects Cerenkov-light or the luminescence of water is a promising method to measure dose distributions in radiotherapy due to its ability to provide high-resolution images in a short measurement time. However, it is unclear whether optical imaging is possible for neutron beams in water. Although neutrons do not emit light in water, prompt gamma photons or protons produced from the interaction between neutrons and water may emit light. To clarify this point, we measured the light distribution in water during irradiation of neutron beams from a boron neutron capture therapy (BNCT) system and compared the result with that calculated by Monte Carlo simulation. The light distribution was measured in a black box using a cooled charge-coupled device (CCD) camera during irradiation of neutrons to water for 5 s from a cyclotron-based clinical BNCT system. In the measured optical image in water, clear light distribution could be observed during neutron beam irradiation. The depth and lateral profiles of the optical images were well-matched with those calculated by simulation for produced Cerenkov-light by the secondary electrons from prompt gamma photons. The simulated Cerenkov-light was nearly identical to that of the dose for prompt gamma photons. We conclude that the optical imaging of a neutron beam is possible and that it might be used for the dose distribution measurements of prompt gamma photons produced by the nuclear interactions between neutrons and water in addition to the gamma photons from the port and collimator. Highlights: Optical imaging of neutron beam has potential for the gamma dose distribution measurements. Optical image was measured during irradiation of neutron beams from a boron neutron capture therapy (BNCT) system. Measured image was well-matched with that calculated by Monte Carlo simulation. The observed optical image attributed to Cerenkov-light from the secondary electrons of prompt gamma produced by nuclear reactions.